2022
DOI: 10.3389/fnagi.2022.943702
|View full text |Cite
|
Sign up to set email alerts
|

Polygenic hazard score modified the relationship between hippocampal subfield atrophy and episodic memory in older adults

Abstract: BackgroundUnderstanding genetic influences on Alzheimer’s disease (AD) may improve early identification. Polygenic hazard score (PHS) is associated with the age of AD onset and cognitive decline. It interacts with other risk factors, but the nature of such combined effects remains poorly understood.Materials and methodsWe examined the effect of genetic risk and hippocampal atrophy pattern on episodic memory in a sample of older adults ranging from cognitively normal to those diagnosed with AD using structural … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Damage to the hippocampal fimbria can disrupt the cholinergic system and cause spatial orientation difficulties and memory deficits in animals ( Cassel et al, 1997 ). Smaller hippocampal fimbria volume was associated with poorer cognitive function in patients with Alzheimer’s disease ( Evans et al, 2018 ; Xu et al, 2022 ). This may be related to its anatomical connections and functional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Damage to the hippocampal fimbria can disrupt the cholinergic system and cause spatial orientation difficulties and memory deficits in animals ( Cassel et al, 1997 ). Smaller hippocampal fimbria volume was associated with poorer cognitive function in patients with Alzheimer’s disease ( Evans et al, 2018 ; Xu et al, 2022 ). This may be related to its anatomical connections and functional pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The fimbria, part of the hippocampus, plays a crucial role in the input and output pathways of the hippocampus. A previous study has suggested that a smaller fimbria is associated with poorer cognitive function in patients with AD (61). This association may be related to the fimbria's anatomical connections and functional pathways.…”
Section: Subcortical Morphological Alterationmentioning
confidence: 91%